Intraoperative radiotherapy as a boost during breast-conserving surgery using low-kilovoltage X-rays: the first 5 years of experience with a novel approach - Wenz, Frederik; Welzel, Grit; Sperk, Elena; Hermann, Brigitte; Steil, Volker; Sütterlin, Marc; Kraus-Tiefenbacher, Uta (International journal of radiation oncology, biology, physics, 2010)
Purpose - Intraoperative radiotherapy (IORT) during breast-conserving surgery (BCS) has been recently introduced using different devices. We report the first 5 years of a single-center experience after introduction of a novel approach to deliver IORT as a tumor bed boost during BCS for breast cancer. - Methods and Materials - A total of 155 breast cancers in 154 women (median age, 63 years; range, 30-83 years; T1/T2 = 100/55; N0/N+ = 108/47) were treated between February 2002 and December 2007 at the University Medical Center Mannheim, in whom IORT as tumor bed boost was applied using 50-kV X-rays (20 Gy) followed by 46-50 Gy whole-breast external-beam radiotherapy (EBRT). Chemotherapy, if indicated, was given before EBRT. The median interval between BCS plus IORT and EBRT was 40 days. Median follow-up was 34 months (maximum 80 months, 1 patient lost to follow-up). Overall survival and local relapse-free survival were calculated at 5 years using the Kaplan-Meier method. Seventy-nine patients were evaluated at 3-year follow-up for late toxicity according to the Late Effects in Normal Tissues-Subjective, Objective, Management, and Analytic system. - Results - Ten patients died, 2 had in-breast relapse, and 8 developed distant metastases (5-year overall survival = 87.0%; 5-year local relapse-free survival = 98.5%). Grade 3 fibroses of the tumor bed were detected in 5% of the patients after 3 years. Skin toxicity was mild (telangiectases and hyperpigmentations in approximately 6% each). - Conclusions - Intraoperative radiotherapy as a tumor bed boost during BCS for breast cancer using low-kilovoltage X-rays followed by EBRT yields low recurrence and toxicity rates.
Gesehen am 16.11.2023